Pervaporation of benzene/cyclohexane mixtures through aromatic polyamide membranes - Wang, Y-Ch.; Li, Ch-L.; Huang, J.; Lin, Ch.; Lee, K-R.; Liaw, D.-J.; Lai, J.-Y.
A series of novel aromatic polyamides based on the 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane (BAPPH)and 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPPP)with various aromatic diacids were investigated for pervaporation separation of benzene/cyclohexane binary system. The aromatic polyamide membranes exhibited a benzene-permselectivity for all the feed compositions and the permeation rate increased with increasing benzene in the feed solution. The fluorine-containing polyamide membranes were swollen in benzene but only slightly in cyclohexane. A separation factor toward benzene, a permeation rate, and a pervaporation separation index (PSI)value through the fluorine-containing polyamide membrane (F-3)for a 50 wt.
Keywords: FLUORINE-CONTAINING AROMATIC POLYAMIDES; BENZENE/CYCLOHEXANE; PERVAPORATION; MEMBRANE